Pneumocystis jirovecii pneumonia complicating methotrexate treatment in a patient with low-risk post-molar gestational trophoblastic neoplasia: A case report and review of the literature - Hector S. Porragas-Paseiro; Steven Johnson; Lindsay Brubaker; Brooke E. Sanders (Elsevier, 2023)
Low-risk gestational trophoblastic neoplasia (GTN) is generally treated with single agent chemotherapy, including methotrexate (MTX) or dactinomycin. We present a case of a patient with low-risk GTN who underwent single agent MTX therapy, developed Pneumocystis jirovecii pneumonia (PJP), recovered, and ultimately completed consolidation treatment for GTN on single agent MTX. While MTX administration is associated with an increased risk of PJP, this association is best described in rheumatology literature. This is the first case of PJP complicating MTX therapy within the gynecologic oncology literature.